Buried Treasure: Contradictions in the Perception and Reality of Women's Leadership - Hopkins, Margaret M.; O'Neil, Deborah Anne; Bilimoria, Diana; Broadfoot, Alison (Frontiers in Psychology, 2021)
The impact of gender on assessments of leadership performance and leadership potential was examined through two clusters of leadership behaviors, one set related to traditional constructions of leadership labeled directing others and another associated with contemporary constructions of leadership labeled engaging others. Based on data collected from a sample of 91 senior leaders in one US financial services organization over a three-year period prior to Covid-19, the results showed a negative relationship between directing others behaviors and leadership potential ratings for females and a positive relationship between these variables for males. A negative relationship between engaging others behaviors and performance assessments was also found for females. This study highlights the continuing bias in leadership assessments of women and explores the contradictions between the perception and the reality of women’s leadership.